2020
DOI: 10.1038/s41467-020-15467-7
|View full text |Cite
|
Sign up to set email alerts
|

A salvage pathway maintains highly functional respiratory complex I

Abstract: Regulation of the turnover of complex I (CI), the largest mitochondrial respiratory chain complex, remains enigmatic despite huge advancement in understanding its structure and the assembly. Here, we report that the NADH-oxidizing N-module of CI is turned over at a higher rate and largely independently of the rest of the complex by mitochondrial matrix protease ClpXP, which selectively removes and degrades damaged subunits. The observed mechanism seems to be a safeguard against the accumulation of dysfunctiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
124
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 52 publications
12
124
0
5
Order By: Relevance
“…Our observations indicate preserved Complex III but lower Complex I activity. Possibly, protein half-life is prolonged when proteins are assembled into a complex, and more so for Complex III than for Complex I whose N module, which protrudes into the matrix, is susceptible to greater turnover (Szczepanowska, Senft et al, 2020). Yet, differential protein degradation might not fully explain our findings because protein levels of SDHB and Complex II in-gel activity, though decreased, were higher than might be expected given the relatively short half-life of Complex II subunits (Fornasiero et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our observations indicate preserved Complex III but lower Complex I activity. Possibly, protein half-life is prolonged when proteins are assembled into a complex, and more so for Complex III than for Complex I whose N module, which protrudes into the matrix, is susceptible to greater turnover (Szczepanowska, Senft et al, 2020). Yet, differential protein degradation might not fully explain our findings because protein levels of SDHB and Complex II in-gel activity, though decreased, were higher than might be expected given the relatively short half-life of Complex II subunits (Fornasiero et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In CLPP-deficient mice, reduced protein levels in complex I subunits have also been observed (Deepa et al, 2016;Szczepanowska et al, 2016). Recently, it was discovered that turnover of the N-module within BN-PAGE-purified intact mitochondrial complexes was faster in proliferating than in differentiated mammalian cell cultures (Szczepanowska et al, 2020). It was proposed that ClpXP protease plays a key role in complex I maintenance, acting through surveillance and replacement of expended N-modules (Szczepanowska et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was discovered that turnover of the N-module within BN-PAGE-purified intact mitochondrial complexes was faster in proliferating than in differentiated mammalian cell cultures (Szczepanowska et al, 2020). It was proposed that ClpXP protease plays a key role in complex I maintenance, acting through surveillance and replacement of expended N-modules (Szczepanowska et al, 2020). It was shown that to regenerate stalled complex I, ClpXP can recognize, disassemble, and rapidly degrade impaired N-module proteins, allowing an effective replacement of N-module components in preexisting complex I (Szczepanowska et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it indicates an important role for NDUFC2 in the assembly of the membrane arm of complex I, particularly involving the ND2 module and, possibly, the ND1 module. Complexome profiling of complex I‐deficient subject cell lines continues to be a useful tool in elucidating the molecular mechanisms underlying complex I assembly and stability (Szczepanowska et al , 2020).…”
Section: Discussionmentioning
confidence: 99%